Investigating the Impact of Training Program on Generative AI Applications in Improving University Teaching - Mashael Awadh Al-Saiari; Yusra Mohammed Al-Mughairiyah; Basmah Nasser Al-Mashaikhiya; Badri Abdulhakim Mudhsh (Qubahan Academic Journal)
Recent innovations in artificial intelligence (AI) have had a profound impact on higher education, as they have on many other aspects of human existence. The current study aimed to investigate the impact of a training program on generative AI applications in enhancing lecturers' teaching capabilities in higher education in the Sultanate of Oman. The study adopted a mixed-methods approach, utilizing both quasi-experimental and qualitative methods. Data were collected through pre- and post-tests conducted on a sample of 31 lecturers from higher education institutions in the sultanate of Oman, and interviews were conducted with six participants in the training program. The results showed a significant positive impact of the program, with significant statistical differences in post-test measurements compared to pre-test measurements and high effect sizes. The interviews also revealed a consensus among participants on the significant impact of the training program on improving teaching capabilities using generative AI applications. The study suggested providing specialized training programs focusing on generative AI applications, implementing educational programs dedicated to generative AI, and strengthening international collaboration in this domain. Based on the findings, the study provided suggestions and recommendations to address the impact of the training program on the use of generative AI applications for developing teaching methods among Omani lectures and beyond.